2017
DOI: 10.1021/acssuschemeng.7b00239
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in Lignin Upgrading by a Combination of Cu-Based Mixed Oxide and Ni-Phosphide Catalysts in Supercritical Ethanol

Abstract: The depolymerization of lignin to bioaromatics usually requires a hydrodeoxygenation (HDO) step to lower the oxygen content. A mixed Cu–Mg–Al oxide (CuMgAlOx) is an effective catalyst for the depolymerization of lignin in supercritical ethanol. We explored the use of Ni-based cocatalysts, i.e. Ni/SiO2, Ni2P/SiO2, and Ni/ASA (ASA = amorphous silica alumina), with the aim of combining lignin depolymerization and HDO in a single reaction step. While the silica-supported catalysts were themselves hardly active in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
(128 reference statements)
1
22
0
Order By: Relevance
“…An efficient one-pot process by combining both lignin depolymerization and hydrodeoxygenation was developed using a combination of Cu-Mg-Al mixed oxide with various Ni-based catalysts (Ni/SiO 2 , Ni 2 P/SiO 2 , and Ni/amorphous silica-alumina). 380 Results indicated that monomer yield and product selectivity were highly dependent on the nature of Ni catalyst. Chen et al 381 found that oxygen vacancies and Mo 6+ together with Mo 5+ species, formed during the partial pre-reduction treatment, act as the active sites for lignin depolymerization in supercritical ethanol.…”
Section: Valorization Of Lignin and Its Derived Compoundsmentioning
confidence: 99%
“…An efficient one-pot process by combining both lignin depolymerization and hydrodeoxygenation was developed using a combination of Cu-Mg-Al mixed oxide with various Ni-based catalysts (Ni/SiO 2 , Ni 2 P/SiO 2 , and Ni/amorphous silica-alumina). 380 Results indicated that monomer yield and product selectivity were highly dependent on the nature of Ni catalyst. Chen et al 381 found that oxygen vacancies and Mo 6+ together with Mo 5+ species, formed during the partial pre-reduction treatment, act as the active sites for lignin depolymerization in supercritical ethanol.…”
Section: Valorization Of Lignin and Its Derived Compoundsmentioning
confidence: 99%
“…We discussed and explained the synergistic and cooperative activation of this optimized two-catalysts system in terms of monomeric product yield and HDO selectivity in more detail in a recent paper [39]. Briefly, the synergy relates to the in situ production of hydrogen by the CuMgAlO x component, maintaining the Ni 2 P surface in its active state.…”
Section: Performance Of the Optimized Ni 2 P/sio 2 Catalystmentioning
confidence: 99%
“…For example, about 55 % and 35 % yields of 4‐n‐propanolsyringol (based on Klason lignin) were obtained via hydrogenolysis of transgenic poplar and birch lignin, respectively . Such high yields of single product were contributed to stabilized pretreatment and effective catalysts which worked not well under harsher conditions ,,. Those results indicate that C3‐phenols are the only phenols that are promising to industrial production.…”
Section: The Promising Products From Lignin Depolymerizationmentioning
confidence: 99%